Foliar Application of Steinernema yirgalemense to Control Planococcus ficus: Assessing Adjuvants to Improve Efficacy - Platt, T.; Stokwe, N.F.; Malan, A.P. (South African Journal of Enology and Viticulture, 2018)
The vine mealybug (Planococcus ficus) is regarded as a key mealybug pest of grapevines in South Africa, with entomopathogenic nematodes (EPNs) being touted as a potential alternative to chemical control, although their vulnerability to above-ground environmental conditions has limited their use. In this study, tests were conducted to assess the ability of adjuvants to increase the deposition of S. yirgalemense on grapevine leaves. The combination of Nu-Film-P® and Zeba® resulted in significantly more infective juveniles (30) being deposited per 4 cm2 leaf disc than with either the control (14.8), or with Nu-Film-P® (23.3), although not significantly more than with Zeba® alone (29.2). The ability of S. yirgalemense, in conjunction with the two adjuvants, to control P. ficus on grapevine foliage was then assessed under controlled conditions. The application of S. yirgalemense with both Zeba® and Nu-Film-P® to P. ficus on leaf discs in a growth chamber resulted in 84% mortality, significantly greater than that attained by the application of S. yirgalemense with either Zeba® (47%), or water alone (26%). Similar results were observed in a glasshouse trial, in which the combination of S. yirgalemense, Zeba® and Nu-Film-P® offered 88% control of P. ficus on leaf discs hung on potted vines, compared with the control that was achieved with S. yirgalemense with either Zeba® (56%) or water alone (30%). This study demonstrates the potential of a combination of S. yirgalemense with adjuvants to give significant control of P. ficus on grapevine foliage, compared with using EPNs alone.